Optimising of Scenedesmus sp. biomass production in chicken slaughterhouse wastewater using response surface methodology and potential utilisation as fish feeds - Yaakob, Maizatul Azrina; Radin Mohamed, Radin Maya Saphira; Al-Gheethi, Adel; Tiey, Athirah; Mohd Kassim, Amir Hashim (Springer, 2019)
Production of Scenedesmus sp. biomass in chicken slaughterhouse wastewater (CSWW) is a promising alternative technique for commercial culture medium due to the high nutritional content of the generated biomass to be used as fish feeds. The current work deals with optimising of biomass production in CSWW using response surface methodology (RSM) as a function of two independent variables, namely temperature (10-30 °C) and photoperiod (6-24 h). The potential application of biomass yield as fish feeds was evaluated based on carbohydrate, protein and lipid contents. The results revealed that the best operating parameters for Scenedesmus sp. biomass production with high contents of carbohydrates, proteins and lipids were determined at 30 °C and after 24 h. The actual and predicted values were 2.47 vs. 3.09 g, 1.44 vs. 1.27 μg/mL, 29.9 vs. 31.60% and 25.75 vs. 28.44%, respectively. Moreover, the produced biomass has a high concentration of fatty acid methyl ester (FAME) as follows: 35.91% of C15:1; 17.58% of C24:1 and 14.11% of C18:1N9T. The biomass yields have 7.98% of eicosapentaenoic acid (EPA, C20:5N3) which is more appropriate as fish feeds. The Fourier transform infrared (FTIR) analysis of biomass revealed that the main functional groups included hydroxyl (OH), aldehyde (=C-H), alkanes and acyl chain groups. Scanning electron micrograph (SEM) and energy-dispersive X-ray spectroscopic analysis (EDS) indicated that the surface morphology and element distribution in biomass produced in BBM and CSWW were varied. The findings have indicated that the biomass produced in CSWW has high potential as fish feeds.